Growth of magnetic cobalt hexacyanoferrate nanoparticles onto bacterial cellulose nanofibers - Sábio, Rafael Miguel; da Silva, Robson Rosa; Sargentelli, Vagner [UNESP]; Gutierrez, Junkal; Tercjak, Agnieszka; Ribeiro, Sidney José Lima [UNESP]; da Silva Barud, Hernane (Springer Nature, 2019)
Natural polymers templates capable to maneuver the growth and spatial distribution of functional nanoparticles have been furthering the development of a new generation of sustainable and versatile materials. Pure cellulose nanofibrils, biosynthesized by bacteria, naturally deliver a 3D interconnected network of lightweight, foldable and sustainable matrices. Cellulose membrane is an exceptional biodegradable and biocompatible and high mechanical strength substrate with a native fibrous structure that can be easily applied as a structure-directing host to produce nanosized materials with optical, electrical or magnetic properties. In this work, we investigated the preparation of magnetic membranes by using bacterial cellulose nanofibers to control the growth of molecule-based magnetic nanoparticles such as Prussian Blue analogs. Magnetic Cobalt–Prussian Blue (CoHCEFe) nanoparticles were synthesized in situ by hydrothermal method through a diffusion-limited precipitation process onto a bacterial cellulose nanofiber network. Scanning electron microscopy and atomic force microscopy clearly unveiled a homogeneous distribution of immobilized COHCEFe crystalline nanoparticles whose size ranges from 94 to 70 nm as a function of nanoparticle content (up 28 wt%). Magnetic force microscopy showed that these nanometric COHCEFe crystalline nanoparticles well dispersed in BC fibers network respond to the magnetic field applied to the MFM-tip. This nano/nano association approach can provide functionally advanced materials for application in catalysis, adsorption of radionuclides, energy generation, data storage, biosensing, optical and magnetic devices.